2009
DOI: 10.1016/j.ejcts.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of cerebral emboli during percutaneous endocardial pulmonary vein isolation versus a thoracoscopic epicardial approach

Abstract: Cerebral micro-emboli during epicardial ablation are almost absent when compared to the thousands of emboli measured during percutaneous endocardial ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Two other studies reported on cerebral microembolization detected by TCD during different AF ablation approaches recently. 10,20 In concordance with the MRI data, the number of MESs in these studies was dependent on the ablation technology. This is the first study to our knowledge, which has also provided data regarding the composition of these microemboli by demonstrating that the majority of them are gaseous, solid particles occurring in <20% of them, regardless of the technology and the anticoagulation scheme used.…”
Section: Discussionsupporting
confidence: 70%
“…Two other studies reported on cerebral microembolization detected by TCD during different AF ablation approaches recently. 10,20 In concordance with the MRI data, the number of MESs in these studies was dependent on the ablation technology. This is the first study to our knowledge, which has also provided data regarding the composition of these microemboli by demonstrating that the majority of them are gaseous, solid particles occurring in <20% of them, regardless of the technology and the anticoagulation scheme used.…”
Section: Discussionsupporting
confidence: 70%
“…The PVI procedure can be performed with either catheter ablation or surgical ablation. Sauren and colleagues 16 investigated the occurrence of cerebral microembolic signals as a surrogate marker for the risk of neurological impairment of two different PVI methods: percutaneous endocardial RF ablation and thoracoscopic epicardial ablation using RF energy.…”
Section: Minimally Invasive Surgery For Lone Atrial Fi Brillationmentioning
confidence: 99%
“…Sauren et al reported reduced incidence of cerebral microembolic signals during thoracoscopic epicardial pulmonary vein isolation compared to percutaneous endocardial ablation. 55 However, currently available strategies for epicardial ablation are significantly invasive, making them undesirable for the majority of patients. Future innovations focussed on minimally invasive percutaneous epicardial ablation are required.…”
Section: Recent Studies Remaining Challenges and Future Considerationsmentioning
confidence: 99%